Help:

\(1) \sqrt{(x-1)^2} = 1 -x \)

\(2) \sqrt{(y^6)} = -y^3\)

\(3) \sqrt{(1+(\sqrt{2 + \sqrt{n})})} = 2\)

Thanks so much! Please explain. I got the answers but weren't sure if they are correct.

HelpPls Jul 8, 2018

#1**0 **

3)

Solve for n:

sqrt(sqrt(sqrt(n) + 2) + 1) = 2

Raise both sides to the power of two:

sqrt(sqrt(n) + 2) + 1 = 4

Subtract 1 from both sides:

sqrt(sqrt(n) + 2) = 3

Raise both sides to the power of two:

sqrt(n) + 2 = 9

Subtract 2 from both sides:

sqrt(n) = 7

Raise both sides to the power of two:

**n = 49**

Guest Jul 8, 2018

#2**0 **

Remember that square rooting is equivalent to raising to the power of a half.

1. The operations would cancel leaving x-1

2. This would be (y^{6})^{1/2 }which, using the power law of indices, would leave y^{3}

3. We would need to square each side, subtract 1 from each side, square each side, subtract 2 from each side and then square each side, in that order. That would leave n=49

Guest Jul 8, 2018